Negotiation Parameters Of Needs Versus Interest Towards Sustainability Of Halal Talents In Malaysia - Norhayati Rafida Abdul Rahim; Muhammad Nizam Awang; Noor Azrina, Y.; Siti Zubaidah, M.; Safiyyah, Ahmad Sabri; Jusang Bolong; Nitty Hirawaty, Kamarulzaman (Academic Inspired Network, 2024)
Indexed by WOS/Scopus/ERA